Electron microscopic changes of the liver following exposure to organic arsenic - Mohd Nazri, Liyana; Saharudin, Shahida; Afeez Adekunle, Ishola; A.Talib, Norlelawati; Muhammad, Siti Aeshah @ Naznin; Buyong, Zunariah; Mohamed, Rozilah @ Abdul Hadi; Myint, Yi Yi; Samsuddin, Niza; Abdul Ghani, Radiah; Abdullah, Nor Zamzila (2017)
BACKGROUND/AIM: There has been a growing concern over the toxicity of organic arsenic to the human body since recent studies indicated these compounds might be at least as toxic as inorganic arsenic. The liver is the primary site of metabolism of arsenic. Therefore it is highly susceptible to the adverse effects of both organic and inorganic arsenic. We aimed to identify any morphological changes in the liver associated with organic exposure on scanning electron microscopy (SEM) and transmission electron microscopy (TEM).